Selection of culture conditions through manipulation of physical and chemical parameters for production of high-value metabolites in marine microalga Tetraselmis tetrathele (West) butcher 1959 biomass - Abd Wahab, Nurul Farahin (2021)
Microalgae cultivation is one of the crucial aspects in the commercialization of microalgae to produce a high amount of biomass and metabolites. In the aquaculture industry, microalgae biomass is used as feed and growth enhancers, and it is also considered a renewable and sustainable resource. Commercially, Tetraselmis sp. is one of the most commonly used microalgae in the aquaculture field. Although there are several studies on the benefits and culture conditions of Tetraselmis sp., little information is known about the understanding of theoretical and technical knowledge on mass culture, which can affect biomass productivity and the quality of microalgae biomass produced. The present study aims to obtain key insights of three growth factors considered as major contributors on the effect of microalgae growth: (1) ammonium nitrogen concentration (chemical parameter), (2) light intensity, and (3) culture temperature (physical parameters) for mass production of an indigenous species, Tetraselmis tetrathele under tropical conditions. Bubble column reactors (BCRs) were used to mimic indoor and outdoor conditions in enhancing the growth characteristics of cells, the effect of physiological processes, and the composition of metabolites. Overall, this study revealed that although the growth performance of T. tetrathele decreased under 35 °C, this indigenous species showed excellent self-adaptation capabilities to cope with high ammonium nitrogen (0.87 g L-1) and varying light intensities (up to 1,500 μmol m-2 s-1) by protecting microalgae from photodamage. These characteristics have significant implications for the selection of optimal conditions when designing more efficient microalgae culture systems in tropical conditions. The knowledge obtained from this work can be useful in assessing the applicability of this strain culture and also enhancing the understanding of the physiology of microalgae to sustainably maximize microalgae cultivation. Besides, these findings are particularly useful for relevant stakeholders to efficiently expand commercialization by selecting high-quality biomass production with specific metabolites of interest in T. tetrathele.